Thin endometrium in ivf practice (literature review) - A I Afyan; N V Dolgushina (IP Berlin A.V., 2014)
Thickness and structure of endometrium during the implantation window is one of the main characteristics of IVF efficacy. However, the prediction role and the threshold of endometrial thickness, which contributes to implantation success, is still the controversial question.Objectives. To study the role and diagnosis of thin endometrium in IVF practice on the base of systematic literature review.